Constraining the timing and provenance of the Neoproterozoic Little Willow and Big Cottonwood Formations, Utah: Expanding the sedimentary record for early rifting of Rodinia - Spencer, Christopher; Hoiland, C.W.; Harris, R.; Link, P.K.; Balgord, E.A. (Elsevier BV, 2012)
U–Pb ages of detrital zircon spectra indicate that the Little Willow Formation in the Wasatch Range, Utah, is not a part of a Paleoproterozoic basement complex (~1700–1800 Ma) as previously thought, but is a metamorphosed part of the Big Cottonwood Formation (~750 Ma). The youngest detrital zircon grains in the metamorphic Little Willow and unmetamorphic Big Cottonwood Formations are 750–850 Ma. These young zircons form a small, but persistent population possibly from Rodinia rift-related magmatism. The majority of the zircons are Grenville-age with other smaller populations derived from the Laurentian anorogenic granites, Mazatzal/Yavapai terranes, and Wyoming Craton. The distribution of new U–Pb detrital zircon ages from the Little Willow Formation has a high statistical probability of similarity to the detrital zircon spectra previously reported from both the Big Cottonwood Formation and the Uinta Mountain Group. Based on these similarities, we propose that the Little Willow Formation represents some of the earliest sediment shed into the Uinta rift basin during the earliest-known phases of Rodina break-up in western Laurentia. The Little Willow is not, therefore of Paleoproterozoic or Archean age as is shown on existing geologic maps.Lu–Hf isotopes in detrital zircons from the Little Willow and Big Cottonwood Formations compared with potential source regions provide evidence that the sediment could have been derived from eastern Laurentia and thus requiring a transcontinental river to transport the sediment ~2000 km. The U–Pb and Lu–Hf values from the Little Willow and Big Cottonwood Formations correspond well with the ~1.0 Ga Grenvillian basement, 1.4 Ga A-type Granites intruding the Central and Western Yavapai, evolved portion of the 1.7–1.8 Ga Santaquin Complex, and the 1.6–3.0 Ga Farmington Canyon Complex (Wyoming Craton).